The effectiveness of classroom discourse in improving teachers’ and learners’ classroom practices - Moussa, Ailoum (The International tax journal, 2025)
Classroom discourse represents the cornerstone of the communication process and constitutes a central pillar of teaching and learning interactions between its main actors the teacher and the learner. It functions as a vital medium for reception, discussion, exchange of viewpoints, and the articulation of questions and problems related to educational issues within the classroom setting. This study aims to highlight the value and role of classroom discourse in the teaching–learning process and to identify its most significant learning outcomes for both teachers and learners.